2018
DOI: 10.4236/ojog.2018.84036
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vaginal Progesterone in Prevention of Preterm Labor in Women with Previous History of One or More Previous Preterm Births

Abstract: Objective: To evaluate whether prophylactic administration of 200 mg vaginal progesterone can reduce the incidence of preterm birth in women with documented history of preterm birth <37 weeks of gestation or not. Setting: Obstetrics and Gynecology Department, Zagazig University Hospital, Egypt. Methods: Ninety patients with previous history of preterm birth prior to 37 week presenting with singleton pregnancy between 20 -24 weeks were randomly allocated to receive either the progesterone 200 mg vaginal supposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
3
5
0
Order By: Relevance
“…It was observed in the present study that 21(40%) patients had preterm delivery and the mean gestational age at delivery was 35.5±2.5 weeks in the progesterone group. This finding was consistent with the studies of Patra K et al [14] , Wajid R et al [15] and Abdou AM [16] .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It was observed in the present study that 21(40%) patients had preterm delivery and the mean gestational age at delivery was 35.5±2.5 weeks in the progesterone group. This finding was consistent with the studies of Patra K et al [14] , Wajid R et al [15] and Abdou AM [16] .…”
Section: Discussionsupporting
confidence: 93%
“…In our study, 12(23%) neonates had low birth weight (<2.5kg), while 7(13%) neonates were admitted in NICU. This is comparable to the studies of Patra K et al [14] , Ashoush S et al [12] , Choudhary M et al [17] , Khan S et al [18] and Abdou AM, [16] . In our study, the mean birth weight was significantly higher in the progesterone group as compared to the placebo group [2432±50 gm versus 1978±70 gm, p=0.000].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Even with a shorter cervical length than we reported in our study [mean was 36 mm in our study], vaginal progesterone achieve a statically significant effect difference between study group and control group according to preterm labor. Data were available from 974 women in [17] A.Abdou et al [18] showed that the administration of vaginal suppository progesterone [200 mg, daily] beginning at 20 -24 wks of gestation and continued to 36 wks of gestation can significantly reduce the rate of preterm birth before 37, 32 and 28 wks of gestation among women with previous spontaneous preterm birth specially in earlier gestational ages and increase the mean birth weight. In addition, the rates of RDS and admission to NICU were significantly decreased among infants of women assigned to progesterone treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Centrally, vaginal progesterone was proved to be significantly effective for prevention of PTB in high risk cases [12]. Currently, no evidence exists on which progesterone supplementation can maximize the preventative effects while minimizing the side effects.…”
Section: Discussionmentioning
confidence: 99%